Challenges Implementation of The Permendikbudristek PPKS In 6 Universities In Yogyakarta Province - Anisah, Laili Nur; Anindita (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2025)
Permendikbudristek Number 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments (Permendikbudristek PPKS) is over 3 years old. All universities, both public and private, are required to comply with these regulations.This step was taken by the Ministry of Education and Culture as an effort to encourage a world of education free from sexual violence. Implementing the PPKS Ministerial Education and Culture Regulation is not easy, especially in the process of preventing and handling sexual violence. This article discusses 3 main things, firstly regarding the understanding of higher education academics in Yogyakarta regarding these regulations, secondly the implementation of the PPKS Permendikbudristek and thirdly the challenges faced by the PPKS Task Force. This research uses empirical juridical methods. The PPKS Task Force studied has also carried out efforts to prevent and handle sexual violence, but the priority in implementing these two things depends on the resources the university has. The challenges faced by the PPKS Task Force in prevention efforts include human resources, learning from the Ministry of Education and Culture's PPKS modules, resistance from higher education leaders in forming the PPKS task force, and the lack of clarity regarding the PPKS task force in the university's organizational structure. The challenges in handling sexual violence faced by the PPKS Task Force are that cases stop because the reporter disappears, there is a lack of human resources, a lack of understanding and empathy for the PPKS Task Force, there is a lack of mentoring facilities at universities, lack of centralized handling of sexual violence in the PPKS Task Force, and finally, the system is not yet clear. Evaluation and monitoring of prevention and handling of sexual violence in higher education.